DINOFLAGELLATE CYST ASSEMBLAGES IN SURFACE SEDIMENTS OF THE LAPTEV SEA REGION (ARCTIC OCEAN) AND THEIR RELATIONSHIP TO HYDROGRAPHIC CONDITIONS - De Vernal A.; Henry M.; Hamel D.; Loucheur V.; Peyron O.; Radi T.; Voronina E.; Matthiessen J.; Kunz-Pirrung M.; Mudie P.J.; Rochon A.; Boessenkool K.P.; et al. (My University, 2001)
The occurrence and distribution of dinoflagellate cysts in surface sediments from the Laptev Sea shelf and the adjacent continental margin have been studied in relation to surface water conditions. Assemblages were interpreted by visual inspection and Q-mode factor analysis. The inner Laptev shelf is a type-area for polar environments because of the near absence of relatively warm waters from the Pacific or Atlantic oceans and an extensive seasonal sea-ice cover. Assemblages are of low diversity and are dominated by the cold water taxon Islandinium minutum and related morphotypes. The common occurrence of distinctive polykrikoid cyst morphotypes is an indicator of polar environments. Furthermore, a strong supply of fresh water in summer influences the surface water conditions, and is a major factor controlling the occurrence and distribution of dinoflagellate cysts. The dinoflagellate cysts Nematosphaeropsis labyrinthus and Operculodinium centrocarpum are restricted to the continental margin, suggesting a relation to the inflow of relatively warm Atlantic waters along the Eurasian continental margin. An abundance maximum of Brigantedinium spp. at the shelf break is related to the mean position of the marginal ice zone.